Peran Pemediasi Reputasi Perusahaan pada Pengaruh Intellectual Capital Terhadap Kinerja Bisnis Perusahaan - Erniza, Desri; Widiastuty, Erna (Universitas Negeri Padang, 2024)
Purpose – This research aims to provide empirical evidence (1) Intellectual capital has a positive and significant effect on company business performance. (2) Intellectual capital has a positive and significant effect on company reputation. (3) Company reputation has a positive and significant effect on the company's business performance. (4) The mediating role of company reputation on the influence of intellectual capital on company business performance. Design/methodology/approach – The sample in this research is public companies listed on the Indonesia Stock Exchange for the observation period 2013-2023. Sampling was carried out using purposive sampling technique. Based on sampling, 198 companies were obtained with a total of 1.980 company-year observations. The independent variable in this research is intellectual capital which is measured by human capital, structural capital, employee capital, and relational capital. Meanwhile, the dependent variable is company performance which is proxied by ROA and ATO. Next, the mediating variable of company reputation is measured by market capitalization. The data source used in this research is secondary data using Data stream. Hypothesis testing was carried out using STATA version 17.Findings – Based on the results of the analysis, it was found that (1) Intellectual capital has no effect on the company's business performance. (2) Intellectual capital has no effect on the company's reputation. (3) Company reputation has a positive and significant effect on the company's business performance. (4) Company reputation does not mediate the influence of intellectual capital on company business performance.Originality/value – This research contributes to (1) Adding to the results of the literature review by providing empirical evidence on the issue of the influence of intellectual capital on company business performance which is mediated by company reputation. (2) The results of previous research examining the influence of intellectual capital on company business performance have inconclusive results. (3) Research examining the mediating role of corporate reputation on intellectual capital and corporate business performance in the Indonesian context is still limited. (4) Previous research used the intellectual capital variable measured by human capital, structural capital, and employee capital. However, in research measuring intellectual capital, it is not only measured by human capital, structural capital, and employee capital but using relational capital. The relational capital element is related to agents, customers, suppliers, competitors, partners, clients, shareholders, industry associations, communities, governments and networks.Research limitations/implications – The implications of this research are that the research results have limitations (1) this research uses all public companies on the IDX. Future research should consider industry characteristics. (2) the company reputation variable should consider other measures such as the corporate image index (CII).